Getting started in research: research questions, supervisors and literature reviews. (February 2015) - Macfarlane, Matthew D; Kisely, Steve; Loi, Samantha; Looi, Jeffrey C; Merry, Sally; Parker, Stephen; Power, Brian; Siskind, Dan; Smith, Geoff; Macfarlane, Stephen
Objectives: Research can seem daunting, especially for trainees and early career researchers. This paper focuses on how to formulate and begin a research project such as the RANZCP Scholarly Project. Methods: We outline an approach to framing a research question, developing theses and hypotheses, choosing a supervisor and conducting a literature review. Conclusions: Through systematic planning early career researchers and other clinicians can plan and conduct research suitable for the Scholarly Project or other research activity.